Localization of angiogenic growth factors and their receptors in the human endometrium throughout the menstrual cycle and in recurrent miscarriage - Lash, Gendie E; Innes, Barbara A; Drury, Josephine A; Robson, Stephen C; Quenby, Siobhan; Bulmer, Judith N (Human reproduction (Oxford), 2012)
Angiogenesis is a key feature of endometrial development. Inappropriate endometrial vascular development has been associated with recurrent miscarriage (RM) with increased amounts of perivascular smooth muscle cells surrounding them. In the current study, we have used immunohistochemistry to study temporal and spatial expression of a series of angiogenic growth factors (AGFs) and their receptors; vascular endothelial growth factor (VEGF)-A, VEGF-C, VEGF-D, VEGF-R1, VEGF-R2, VEGF-R3, platelet-derived growth factor (PDGF)-BB, PDGF-Rα, PDGF-Rβ, transforming growth factor (TGF)-β1, TGF-βRI, TGF-βRII, angiopoietin (Ang)-1, Ang-2 and Tie-2, in the proliferative, early secretory and mid-late secretory phase endometrium from control women as well as in the mid-late secretory phase of women with a history of RM. The AGFs and their receptors studied were immunostained and assessed separately in stromal, vascular smooth muscle, endothelial and glandular epithelial cells. Laser capture microdissection and real-time RT-PCR were used to confirm expression patterns observed by immunohistochemistry. Most AGFs investigated showed both temporal and spatial expression patterns in normal cycling endometrium. In addition, immunostaining intensity for several AGFs was altered in women with a history of RM, particularly in vascular smooth muscle cells (VSMCs). VSMC expression of TGF-β1, VEGF-R1 and VEGF-R2 was increased while expression of PDGF-BB, TGF-βRI, TGF-βRII, Ang-2, VEGF-A and VEGF-C was reduced. This study confirms that the cycling endometrium is a highly angiogenic tissue and that this process is likely to be altered in women with a history of RM and may contribute to the aetiology of this condition.